Intelligent Hybrid Cloud Data Hosting Services with Effective Cost and High Availability - Madhu Bala Myneni; L V Narasimha Prasad; D Naveen Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this Paper the major concentration is an efficient and user based data hosting service for hybrid cloud. It provides friendly transaction scheme with the features of cost effective and high availability to all users. This framework intelligently puts data into cloud with effective cost and high availability. This gives a plan of proof of information respectability in which the client has utilize to check the rightness of his information. In this study the major cloud storage vendors in India are considered and the parameters like storage space, cost of storage, outgoing bandwidth and type of transition mode. Based on available knowledge on all parameters of existing cloud service providers in India, the intelligent hybrid cloud data hosting framework are assured to customers for low cost and high availability with mode of transition. It guarantees that the ability at the customer side is negligible and which will be helpful for customers.